2022
DOI: 10.3390/agronomy12081868
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Morpho-Physiological Traits in Rice Genotypes for Adaptation under Irrigated and Water-Limited Environments

Abstract: Drought is one of the major limitations to rice productivity worldwide. The present study compared variation in seventeen rice genotypes of Egyptian origin for morpho-physiological traits to identify the best genotypes with combination of adaptive traits under water-limited condition (DS). The DS reduced days to heading (DTH), plant height (PH), flag leaf angle (FLA), flag leaf area (FLAR), chlorophyll content (CHC), relative water content (RWC), grain yield (GY), and its components. Among genotypes, Hybrid 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Three levels of drought stress corresponding to 5% (m 3 /m 3 ), 10.6% (m 3 /m 3 ), and 16% (m 3 /m 3 ) soil moisture content, representing severe, moderate, and low drought, respectively, were used by Singh et al [ 14 ] to assess the response of rice cultivars to early-season drought stress. Different methods of screening rice genotypes for drought tolerance have been used by researchers through classical markers or DNA/molecular markers [ 15 , 16 ]. Depending on the specific objective, each type of marker may present advantages and/or disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Three levels of drought stress corresponding to 5% (m 3 /m 3 ), 10.6% (m 3 /m 3 ), and 16% (m 3 /m 3 ) soil moisture content, representing severe, moderate, and low drought, respectively, were used by Singh et al [ 14 ] to assess the response of rice cultivars to early-season drought stress. Different methods of screening rice genotypes for drought tolerance have been used by researchers through classical markers or DNA/molecular markers [ 15 , 16 ]. Depending on the specific objective, each type of marker may present advantages and/or disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Plants with an appropriate canopy shape can capture light resources optimally and have a high value of solar radiation use efficiency [28]. Plants with these characteristics can produce higher biomass and daily grain yields following the results of previous studies, which stated that the high production capacity of biomass before or after the heading stage is a characteristic of high-yielding rice [25,26,31]. The rate of photosynthesis and SPAD value can be vital selection characteristics in the MCRC system.…”
Section: Resultsmentioning
confidence: 68%
“…For example, exposure of wheat plants to drought during post-anthesis stage, it either repressed grain maturation or left the grain completely unfilled (Dhanda & Sethi, 2002;Thakur et al, 2010) while when exposed during pre-anthesis stage cultivars showed increased drought tolerance at seed filling stage (Wang et al, 2014(Wang et al, , 2015. The drought stress during panicle initiation and flowering stages in rice leads to drastic reduction in spikelet and grain number per panicle (Ghoneim 2018(Ghoneim , 2020Gaballah et al, 2022;Ishimaru et al, 2022). Some plants employ drought escape strategies by favoring early flowering, increased growth rate, higher photosynthesis capacity and preservation of reserves for seed development (Gaballah et al, 2022).…”
Section: Floweringmentioning
confidence: 99%
“…The drought stress during panicle initiation and flowering stages in rice leads to drastic reduction in spikelet and grain number per panicle (Ghoneim 2018(Ghoneim , 2020Gaballah et al, 2022;Ishimaru et al, 2022). Some plants employ drought escape strategies by favoring early flowering, increased growth rate, higher photosynthesis capacity and preservation of reserves for seed development (Gaballah et al, 2022). Flowering, vegetative and seed maturation stages of maize are most vulnerable to water scarcity, causing yield loss up to 50, 25 and 21% respectively (Sah et al, 2020).…”
Section: Floweringmentioning
confidence: 99%